2019
DOI: 10.15570/actaapa.2019.15
|View full text |Cite
|
Sign up to set email alerts
|

Cryosurgery to remove perichondrium for the rabbit ear hypertrophic scar model: a simplified method

Abstract: In this study, we hypothesized whether cryosurgery could be used effectively for the removal of perichondrium in a simpler and easily reproducible model instead of the previously described conventional surgery. Methods The study was carried out with the approval of the Animal Experimentation Ethics Committee of our institution (no. 14/190). Six young male New Zealand white rabbits (3,000 to 3,500 g) were used. The animals were kept under standardized housing and animal care conditions following the guidelines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…To create up to 12 hypertrophic scars per animal according to this model, wounds must have at least a diameter of 7 mm, and the perichondrium must be removed, which is associated with a delayed re-epithelialization and an enhanced formation of scar tissue [15,38,46]. Removal of the perichondrium may be achieved by conventional surgery, but cryosurgery lowers the risk of damaging underlying cartilage [16]. Zu et al showed that hypertrophic scarring in rabbits may be induced by subcutaneous injection of anhydrous alcohol into the dorsal trunk [18].…”
Section: Rabbit Modelsmentioning
confidence: 99%
“…To create up to 12 hypertrophic scars per animal according to this model, wounds must have at least a diameter of 7 mm, and the perichondrium must be removed, which is associated with a delayed re-epithelialization and an enhanced formation of scar tissue [15,38,46]. Removal of the perichondrium may be achieved by conventional surgery, but cryosurgery lowers the risk of damaging underlying cartilage [16]. Zu et al showed that hypertrophic scarring in rabbits may be induced by subcutaneous injection of anhydrous alcohol into the dorsal trunk [18].…”
Section: Rabbit Modelsmentioning
confidence: 99%
“…It occurs after skin injuries, especially burns, and can cause severe physical and psychological distress [1,2]. Various medical treatments, including cryotherapy, laser therapy, drug therapy, and compression therapy, are available for HS [3][4][5][6]. However, these treatments may lead to adverse reactions and the appearance of new skin damage [7].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms involved in scar formation in each stage are also different ( Bowers and Franco, 2020 ). At present, there are surgical treatment, physical therapy ( Zhang et al, 2019 ), laser therapy ( Tan et al, 2021 ), cryotherapy ( Tunca et al, 2019 ), and drug therapy ( Bi et al, 2019 ) for HS. Each treatment has its advantages and disadvantages ( Elsaie, 2021 ).…”
Section: Introductionmentioning
confidence: 99%